Influence of Different Rootstocks on Fruit Quality and Primary and Secondary Metabolites Content of Blood Oranges Cultivars - Forner-Giner, María A.; Ballesta-de los Santos, Manuel; Melgarejo, Pablo; Martínez-Nicolás, Juan J.; Nunez-Gómez, Dámaris; Continella, Alberto; Legua, Pilar (MDPI, 2023)
Blood oranges have high concentrations of bioactive compounds that are beneficial to health. In Europe, the cultivation of blood oranges is increasing due to their excellent nutritional properties. In Citrus crops, rootstocks play an important role in juice and can increase the content of bioactive compounds. The morphological, qualitative and nutritional parameters were analyzed in cultivars ‘Tarocco Ippolito’, ‘Tarocco Lempso’, ‘Tarocco Tapi’ and ‘Tarocco Fondaconuovo’ grafted onto Citrus macrophylla and Citrus reshni. ‘Tarocco Lempso’ grafted onto Citrus macrophylla obtained the highest values of weight (275.78 g), caliber (81.37 mm and 76.79 mm) and juice content (162.11 g). ‘Tarocco Tapi’ grafted onto Citrus reshni obtained the most interesting qualitative parameters (15.40 °Brix; 12.0 MI). ‘Tarocco Lempso’ grafted onto Citrus reshni obtained the most intense red juice (a* = 9.61). Overall, the highest concentrations of primary metabolites were in proline, aspartate, citric acid, and sucrose. The results showed that ‘Tarocco Ippolito’ juice grafted onto Citrus reshni had the highest levels of total hydroxycinnamic acids (263.33 mg L−1), total flavones (449.74 mg L−1) and total anthocyanins (650.42 mg L−1). To conclude, ‘Tarocco Lempso’ grafted onto Citrus macrophylla obtained the best values of agronomic parameters, and the cultivars grafted onto Citrus reshni obtained significantly higher concentrations in primary and secondary metabolites.